Prenatal stress induces alterations in cerebellar nitric oxide that are correlated with deficits in spatial memory in rat’s offspring - Maur, Damián Gustavo (2012)
Prenatal stress (PS) has been linked to abnormal cognitive, behavioral and psychosocial outcomes in both animals and humans. Since PS has been shown to induce a cerebellar cytoarchitectural disarrangement and cerebellar abnormalities that have been linked to an impairment of behavioral functions, the aim of the present work was to investigate whether the exposure to PS in a period in which the cerebellum is still immature can induce behavioral deficits in the adult and whether this alterations are correlated with changes in nitric oxide (NO) and cellular oxidative mechanisms in offspring’s cerebellum. Our results show impairments in spatial memory and territory discrimination in PS adult rats. PS offspring also displayed alterations in cerebellar nitric oxide synthase (NOS) expression and activity. Moreover, a correlation between spatial memory deficits and the increase in NOS activity was found. The results found here may point to a role of cerebellar NO in the behavioral alterations induced by stress during early development stages.